Oxytocin Massage as a Supportive Technique to Improve Lactation Among Postpartum Women - Khaeriyah, Hana Nurul; Sari, Ossie Happina (Ahmar Metastasis Health Journal, 2025)
Breast milk is the optimal source of nutrition for infants, yet low milk production during the early postpartum period often hinders the achievement of exclusive breastfeeding. Oxytocin massage is a simple non-pharmacological technique that may support lactation by enhancing the oxytocin reflex and promoting maternal relaxation. This study aimed to examine the association between oxytocin massage and breast milk production among postpartum mothers in the working area of UPTD Puskesmas Ciawi, Tasikmalaya Regency, in 2024. A quasi-experimental one-group pretest–posttest design was used, involving 20 postpartum mothers selected through total sampling. Breast milk production was assessed using objective expressed milk volume and a validated lactation checklist before and after seven consecutive days of oxytocin massage. Data were analyzed using the paired sample t-test following normality verification. The results showed an increase in the proportion of mothers with adequate milk production from 10% at pretest to 80% at posttest, accompanied by a significant rise in mean production scores (p < 0.001; Cohen’s d = 1.32). While these findings suggest that oxytocin massage may support improvements in breast milk production, the absence of a control group limits causal interpretation. Oxytocin massage may nonetheless be considered a complementary, low-cost intervention in postpartum care, and future studies employing randomized controlled designs are recommended to confirm its effectiveness.